1998
DOI: 10.1029/97rs03215
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the ionosphere and neutral atmosphere using artificial periodic inhomogeneities in the ionospheric plasma

Abstract: Abstract. This paper is devoted to a ground-based method for diagnostics of the ionosphere and neutral atmosphere. This method uses one of the numerous physical phenomena observed in the ionosphere illuminated by a high-power radio wave, namely, the generation of artificial periodic inhomogeneities. New results on the ionospheric and atmospheric parameter measurements at E region heights are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The methods of measuring atmospheric parameters by means of resonant scattering of radio waves by artificial periodic irregularities are described in detail in [3,[7][8][9]. They were developed as the effect of high-power high-frequency radio waves on the ionosphere was studied.…”
Section: Methods Of Determining Characteristics Of the Ionosphere And mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of measuring atmospheric parameters by means of resonant scattering of radio waves by artificial periodic irregularities are described in detail in [3,[7][8][9]. They were developed as the effect of high-power high-frequency radio waves on the ionosphere was studied.…”
Section: Methods Of Determining Characteristics Of the Ionosphere And mentioning
confidence: 99%
“…3.2, it is shown that for the linear profile, the temperature gradient values ∂T /∂z < −(10-12) K/km are sufficient for the occurrence of an instability, in accordance with Eqs. (9) and (10). The medium is expected to become turbulent due to the excitation of internal gravity waves of different periods and the rise in their amplitude [29,30].…”
Section: Variations In the Characteristics Of A Neutral Atmosphere Anmentioning
confidence: 99%
“…Currently, API technique is used as method to study the ionosphere and neutral atmosphere. Results of these studies and the theory of API formation and decay are summarized in the monograph [ Belikovich et al ., ] and papers [ Bakhmet ' eva et al ., ; Bakhmetieva and Belikovich , , ; Grigoriev et al ., ; Tolmacheva et al ., ]. APIs were observed at the heating facilities at Arecibo [ Feier et al ., ], High Power Auroral Stimulation (HIPAS) [ Djuth et al ., ], European Incoherent Scatter (EISCAT) [ Rietveld et al ., ; Rietveld and Goncharov , ; Vierinen et al ., ], and High Frequency Active Auroral Research Program (HAARP) [ Hysell et al ., ; Grach et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The creation of artificial periodic inhomogeneities (APIs) [1][2][3][4][5][6][7][8][9][10] in the ionosphere by ground-based, high frequency (HF) modification facilities has been a subject of considerable interest as it plays significant role in geophysical and radio physical phenomena and communication. First, such observation was made by Belikovich et al, 11 in 1975.…”
Section: Introductionmentioning
confidence: 99%